Halal Ecosystem for MSMEs: Assistance with Product Certification to Strengthen the Local Economy - Silfin Aisyah; Wildan Miftahussurur; Saini saini; Sofiatus Sobriyah; Qoidul Khoir (Dedikasi Sosial: Jurnal Pengabdian Masyarakat, 2025)
The community engagement programme on halal certification assistance for cassava-based crackers (lempeng) was carried out in Ledokombo Village, Sumberjambe District, Jember Regency, East Java, Indonesia, with the aim of enhancing halal literacy, improving product quality, and fostering a community-based halal ecosystem. This initiative was motivated by the limited understanding among micro, small, and medium enterprises (MSMEs) of halal certification procedures and the necessity of legal compliance to expand market access. A participatory approach was employed through several stages: awareness-raising sessions, raw material identification, administrative assistance, and technical guidance on packaging and branding.The findings indicate significant improvements in three key areas. First, MSMEs’ halal literacy increased through a deeper understanding of certification procedures and the principles of halal and thayyib production. Second, product quality and competitiveness improved via the adoption of hygienic production standards, the use of certified halal ingredients, and the development of more attractive and informative packaging. Third, a supportive network involving MSMEs, local government, and relevant institutions emerged, reinforcing programme sustainability and strengthening the halal ecosystem at the local level. Moreover, the programme offered experiential learning opportunities for students as change agents, enabling them to develop practical skills in community empowerment. Overall, the halal certification assistance programme in Ledokombo Village, Jember Regency not only facilitated legal compliance but also generated substantial socio-economic impacts, contributing to the national agenda of positioning Indonesia as a global hub for the halal industry.